2016
DOI: 10.1080/09273972.2016.1242636
|View full text |Cite
|
Sign up to set email alerts
|

Normative Values for Near and Distance Clinical Tests of Stereoacuity

Abstract: Normative values for each stereotest are identified and discussed with respect to other studies. Potential sources of variation between tests, within testing distances, are also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…Results from previous studies of near stereoacuity in young adults are also shown. From left to right, these data are from [ 52 ](median), [ 52 ] (average), [ 51 ] (average), [ 53 ] (average), [ 54 ] (average), and [ 53 ] (median). There were no differences in distance VA ( a ), near VA ( b ), or stereoacuity ( c ) between the three samples that participated in this study (all p > 0.10) …”
Section: Resultsmentioning
confidence: 99%
“…Results from previous studies of near stereoacuity in young adults are also shown. From left to right, these data are from [ 52 ](median), [ 52 ] (average), [ 51 ] (average), [ 53 ] (average), [ 54 ] (average), and [ 53 ] (median). There were no differences in distance VA ( a ), near VA ( b ), or stereoacuity ( c ) between the three samples that participated in this study (all p > 0.10) …”
Section: Resultsmentioning
confidence: 99%
“…those featuring the use of polaroid filters, and therefore which do not create rivalrous right and left eye conditions but which, like the TNO, do not contain monocular cues). However, the TNO test is a long-established and recognised means for clinical estimation of stereoacuity [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…After successful cataract surgery in both subjects, normal binocular vision operated to fine degrees in the subject implanted with the multifocal IOL at both distance and near, with their stereopsis within normal limits. 25 The subject with the monofocal IOL showed poor near vision, only gross binocular single vision and the absence of stereopsis, which was reflected in the deteriorated NAVQ results with the monofocal IOL. This suggests that the multifocal IOL was able to complement the accommodative power of the untreated eye, whereas the monofocal IOL could not.…”
Section: Discussionmentioning
confidence: 98%